2018
DOI: 10.1161/jaha.117.008397
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death in Patients With Severe Aortic Stenosis: Observations From the CURRENT AS Registry

Abstract: BackgroundThe annual incidence of sudden death has been reported to be low (<1%/year) in asymptomatic patients with severe aortic stenosis (AS), and there is a paucity of data on the risk factors of sudden death in patients with severe AS.Methods and ResultsWe evaluated the incidence and risk factors of sudden death during the median follow‐up period of 1334 days in the Contemporary Outcomes After Surgery and Medical Treatment in Patients With Severe Aortic Stenosis (CURRENT AS) registry enrolling 3815 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 28 publications
2
30
0
2
Order By: Relevance
“…Valvular heart disease can cause SCD through both mechanical and arrhythmogenic mechanisms. Asymptomatic severe aortic stenosis has traditionally been thought to pose low risk of SCD at around 1% per year but newer data suggest that this figure is likely closer to 5–7% . There has long been an association between mitral valve prolapse and SCD due to ventricular arrhythmias with an estimated risk of 0.2–1.9% but the incidence is poorly defined …”
Section: Causes Of Scdmentioning
confidence: 99%
“…Valvular heart disease can cause SCD through both mechanical and arrhythmogenic mechanisms. Asymptomatic severe aortic stenosis has traditionally been thought to pose low risk of SCD at around 1% per year but newer data suggest that this figure is likely closer to 5–7% . There has long been an association between mitral valve prolapse and SCD due to ventricular arrhythmias with an estimated risk of 0.2–1.9% but the incidence is poorly defined …”
Section: Causes Of Scdmentioning
confidence: 99%
“…Baseline characteristics of the study patients were previously reported in detail 8 10 11. Briefly, among the 3815 patients with severe AS enrolled in this registry, the mean age was 77.8 years, which was much older than in the previous reports,12–15 and 1443 patients (38%) were men.…”
Section: Current As Registrymentioning
confidence: 91%
“…Third, SAVR after symptom development might be carrying higher operative risk than SAVR during the asymptomatic phase 33. Fourth, the annual rate of sudden death during the asymptomatic phase might be higher (1.4%/year) than the rate (<1.0%/year) reported previously 10 13–15. Finally, in the CURRENT AS registry, 41% of patients managed conservatively required AVR within a median follow-up of 2 years, suggesting that one does not gain much by waiting (figure 4).…”
Section: Management Of Asymptomatic Patients With Severe Asmentioning
confidence: 97%
See 1 more Smart Citation
“…Should symptoms develop, clinical deterioration may progress rapidly, and the risk of sudden death can escalate if AS is managed conservatively (4% at 1 month, 12% at 6 months). 20 In a recent study of AS patients with a high probability of LV decompensation, more than 50% were either dead or hospitalised with cardiac failure within 2 years. 21 Timing of intervention is also crucial, as perioperative morbidity is markedly increased if advanced left ventricular systolic dysfunction occurs due to a delay in intervention.…”
Section: What Is the Monthly Mortality On A Tavi Waiting List?mentioning
confidence: 99%